INTEGRATED EDUCATIONAL OPPORTUNITIES IN THE UNIVERSAL MUSEUM: FIVE WAYS FORWARD (Cadernos de Sociomuseologia, 2009)
Whatever the other characteristics of the universal museum, education must be one of its core functions. That is, education both of regular visitors and those who are not but who are members of the local, regional or national communities served by the museum. In this sense, universal refers to making the museum accessible to all: accessible physically and intellectually. This relates to what I mean by education. It is far broader than what takes place between teachers and pupils in a formal setting. Education is also about providing environments where people will be inspired or provoked to know, to question. To reflect about themselves and the wider human and natural world. A universal museum should be a great facilitator of these learning processes. In this paper I shall focus on five ways in which there can be integration of educational opportunities in the universal museum. For examples to illustrate these themes I shall draw on practices in a small sample of museums in Europe and the USA.